Estimation of Compaction Parameters from Sonic Logs Data at Jambur Area North of Iraq - Al-Mukhtar, Khalid; Al-Bahidly, Haydar (Iraqi Journal of Science, 2025)
The present paper deals with estimation of compaction parameters from the empirical relationships relating time and velocity of the propagated sonic waves with depth. For this aim two geologic intervals were chosen at Jambur area, the first one is limited between the top of Fatha formation (M. Miocene) and base of Jeribe formation (L. Miocene) while the second one is limited between the base of Jeribe formation and the top of Qamchuqa formation (Albian – M. Cretaceous). Sonic logs data revealed the existence of two Low Velocity Layers (LVL) in these intervals. They correspond to porous saliferous and seepage beds in the first interval. and to the highly fractured and oil bearing carbonate bed in the second interval.Sonic logs data of 7 oil wells were analyzed and used to compute 77 empirical exponential relations for bath intervals. Of these, the compaction parameters were deduced and interpreted in terms of many parameters like the depth below the top of the interval and the thickness of the LVL.The results indicate the importance of using compaction parameters in the estimation of depth and thickness variations of (LVL).